STAFF TRAINING AND ACADEMICS JOB PERFORMANCE IN TERTIARY INSTITUTIONS IN NIGERIA - Niyi Jacob Ogunode; Conrad Ugochukwu Ukozor; Richmond Chijioke Agbo (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This research explores the nexus between training programs and the job performance of academic staff in Nigerian tertiary institutions, relying on secondary data gleaned from both print and online sources. Through a comprehensive review of publications, we discerned a pivotal relationship between consistent academic staff training and heightened job performance. Our findings underscore the positive impact of training on the effective implementation of teaching, research, and community service programs by academicians. The study's conclusion emphasizes the integral role played by ongoing training initiatives in shaping the performance landscape within tertiary institutions. Academic staff, when equipped with diverse skills through continual training, exhibit enhanced proficiency in executing their responsibilities across teaching, research, and community service realms. This research contributes valuable insights to the discourse on professional development within academic settings. In light of our discoveries, we advocate for the establishment of structured training programs tailored to the unique demands of academic roles. These initiatives, supported by continuous professional development and institutional backing, stand poised to elevate the overall performance of academic staff in Nigerian tertiary institutions. This paper serves as a call to action for educational institutions to prioritize training as a strategic investment in the advancement of higher education in Nigeria.